Grb2 Y160F mutant mimics the wild-type monomeric state dynamics and the monomer-dimer equilibrium - Casteluci, G. [UNESP]; Dias, R. V.R. [UNESP]; Martins, I. B.S. [UNESP]; Fernandes, R. A.; Tedesco, J. A. [UNESP]; Caruso, I. P. [UNESP]; de Araujo, A. S. [UNESP]; Itri, R.; Melo, F. A. [UNESP] (Elsevier, 2024)
The Growth factor receptor-bound protein 2 (Grb2) participates in early signaling complexes and regulates tyrosine kinase-mediated signal transduction through a monomer-dimer equilibrium. Grb2 dimeric state inhibits signal transduction whereas the monomer promotes signaling downstream. Since Grb2 dimer KD is ∼0.8 μM, studies focused on the monomer are still challenging and require mutations or interaction with phosphotyrosine peptides. However, these mutants were never characterized considering their effects on protein structure and dynamics in solution. Here, we present the biophysical characterization of Grb2Y160F, the first Grb2 mutant to induce protein monomerization without disrupting its native behavior in solution due to net charge modifications or interaction with peptides. We also identified that Grb2Y160F exists in a monomer-dimer equilibrium. Grb2Y160F ability to dimerize implies that different dimerization interfaces might regulate signaling pathways in distinct ways and raises an important question about the role of the Y160 residue in other dimerization interfaces.
Keywords: Grb2 monomer; Grb2 Y160F; Monomer-dimer equilibrium